FORMULASI DAN UJI EFEKTIVITAS MOUTHWASH KOMBINASI DAUN BINAHONG DAN DAUN KEMANGI - Isnaeni Usman; Ismail Ismail; Jane Stefany Rambung; Ermi Reski Hijriah AR (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
Dental caries and bad breath are oral health problems that are complaints by teenagers and children caused by Streptococcus mutans which is normal flora bacteria in the oral cavity but in large numbers, these bacteria can trigger the formation of dental plaque. This study aims to compare the antibacterial effectiveness of a single extract and extracts combination formulated in mouthwash. Basil and madeira-vine leaves are known to have antibacterial activity against several bacteria, one of them is Streptococcus mutans. Simplicia of madeira-vine and basil leaves were extracted by maceration using 70% ethanol and phytochemical screening tests has done on the extracts produced. Mouthwash formulation is performed using the bottle method and antibacterial activity test and its effectiveness are carried out using the agar diffusion method. Phytochemical screening result shows that basil leaves extract contains alkaloid and flavonoid, while madeira-vine leaves extract contains alkaloid and phenolic compounds. A single extract at a concentration of 7% had the most optimal inhibition of Streptococcus mutans while in the combination of extracts, the most optimal concentration ratio was shown at an extracts combination of madeira-vine : basil leaves 70:30. Mouthwash preparations are formulated in several formulas namely F1, F2, F3. Tests carried out before and after storage were expedited showing that F3 (a combination formula of madeira vine leaves extract : basil leaves 70:30) is the most stable and effective formula in inhibiting Streptococcus mutans.